Penyuluhan Penerapan Teknologi Tepat Guna Dalam Pemeliharaan Ayam KUB Untuk Meningkatkan Produktivitas Peternak Rakyat - Multazam, Syamsul; Haryanti, Ramdani; Islami, Gita Nabilla; Aini, Aini; Al-Ayuni, Yusfi; Ariani, Nining; Zaki, Muhammad; Fakhrurrozi, Fakhrurrozi; Mahendra, Rizki Adi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
Balitbangtan Superior Village Chicken (KUB) is one of the innovation results in the development of local poultry that has high prospects as a source of animal protein and income for village communities. This community service activity was carried out to improve the knowledge and skills of farmers regarding appropriate technology in raising KUB chickens. The program implementation method was carried out from September 1 to November 31, 2025 with a participatory approach through the stages, 1) Socialization and Needs Identification, 2) Technical Counseling and Training, 3) Continuous Mentoring and Monitoring and 4) Evaluation and Feedback. This Community Service Activity has been implemented in Pejanggik Village, Central Lombok Regency on Monday, September 1, 2025. The technologies applied are, 1) Cage Technology, 2) Hatching Technology, 3) Feed Technology, 4) Health and Management Technology. The results of the implementation showed a significant increase in the skills and understanding of partners. The average pretest score of 52.5% increased to 94.75% in the posttest. The success rate for implementing cage technology increased from 65% to 94%, hatching technology from 50% to 90%, feeding technology from 55% to 97%, and health and management technology from 55% to 98%. Furthermore, the partner satisfaction questionnaire scored 95% (very satisfied). In conclusion, this program not only improves the technical aspects of KUB chicken farming but also empowers the community.